Safety and efficacy of sorafenib for the treatment of recurrent hepatocellular carcinoma after liver transplantation. (13th June 2013) - Waghray, Abhijeet; Balci, Bengi; El‐Gazzaz, Galal; Kim, Richard; Pelley, Robert; Narayanan Menon, KV; Estfan, Bassam; Romero‐Marrero, Carlos; Aucejo, Federico
Abstract Introduction Recurrent hepatocellular carcinoma (HCC) following liver transplantation (LT) carries a poor prognosis. The aim of our study was to assess the safety and efficacy of sorafenib in patients with recurrent HCC following LT. Methods A prospectively maintained LT database was retrospectively analyzed for patients with recurrent HCC following LT between 2001 and 2011–34 patients. Patients were divided into two groups based on whether they were prescribed sorafenib (n = 17) or not prescribed sorafenib (n = 17). The primary endpoint was overall survival. Results There were no significant differences between the two groups analyzed. Seventeen patients were on sorafenib for recurrent HCC, with a mean daily dose of ~444 mg. Mean duration of treatment was ~10 months. Side effects included: thrombocytopenia, diarrhea, rising transaminases, fatigue, hand–foot skin reaction, and nausea. Survival in the sorafenib vs. non‐sorafenib group was greater at three‐, six‐, nine‐, and 12‐month intervals and overall survival. Conclusion Sorafenib can be well tolerated and safe in patients with recurrent HCC following LT and may be associated with a modest survival benefit. To our knowledge, this is the largest single‐center retrospective analysis of patients prescribed sorafenib for recurrent HCC after LT.